Slave No More : Self-Liberation before Abolitionism in the Americas - Helg, Aline, 1953- (Book collections on Project MUSE., 2019)
"Commanding a vast historiography of slavery and emancipation, Aline Helg argues that significant numbers of enslaved Africans and their descendants across the entire Western Hemisphere managed to free themselves hundreds of years before the formation of white-run abolitionist movements. Her analysis of resistance and struggle covers more than three centuries, from early colonization to the American and Haitian revolutions, Spanish American independence, and abolition in the British Caribbean. But Helg's purpose is not only to underscore the agency of those who managed to become 'free people of color' before abolitionism took hold but also to assess in detail the specific strategies they created and utilized"--